Biocompatibility of the outer prismatic and the inner nacreous layers of four different molluscs - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
The in vitro biocompatibility of aragonite material obtained from inner and out layers of four different molluscs was tested. After grinding and sieving, the obtained fine powders were put in contact with primary osteoblasts derived from rat calvariae. The viability of the cells increased at about 10% in the presence of powders derived from Vennus Gallina outer layer and from Pecten Jacobaeus inner layer. In the case of the presence of the other 6 tested powders, there was no statistical difference in cells' viability. With regard to alkaline phosphatase production, all the tested powders induced a decrease of the production of this enzyme by osteoblasts. There was no evidence of any alterations in collagen production.
Keywords: molluscs; shells; nacres; aragonite; cell culture; osteoblasts; in vitro biocompatibility; IMPLANTS; BONE